2020
DOI: 10.1111/2041-210x.13429
|View full text |Cite
|
Sign up to set email alerts
|

Calculating effect sizes in animal social network analysis

Abstract: has arisen mainly due to researchers' past tendency to over focus on statistical significance, rather than a balanced consideration of it along with biological importance of model effects. Consequently, there is growing movement towards the use of approaches that place greater emphasis on biological importance through effect sizes, such as model comparisons and Bayesian inference (Burnham, Anderson,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…Recent studies found that (datastream and node) permutation tests, which are widely used to test hypotheses in animal social network analyses, can produce high rates of type I error (false positives) and type II error (false negatives) (Franks et al 2020; Puga□Gonzalez et al 2020; Weiss et al 2020; Farine and Carter 2020). In order to ensure that the results provided by our GAI analyses are reliable and account for both social and non-social nuisance effects, we used an approach proposed by Farine and Carter (2020) that uses datastream permutations to control for nuisance effects, then uses node permutations to test for the statistical significance of the effect of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies found that (datastream and node) permutation tests, which are widely used to test hypotheses in animal social network analyses, can produce high rates of type I error (false positives) and type II error (false negatives) (Franks et al 2020; Puga□Gonzalez et al 2020; Weiss et al 2020; Farine and Carter 2020). In order to ensure that the results provided by our GAI analyses are reliable and account for both social and non-social nuisance effects, we used an approach proposed by Farine and Carter (2020) that uses datastream permutations to control for nuisance effects, then uses node permutations to test for the statistical significance of the effect of interest.…”
Section: Methodsmentioning
confidence: 99%
“…For each run of the simulation, we calculate P values for the effect of the trait value on degree using (1) node permutation tests with the coefficient value as the test statistic, (2) node permutation tests with the coefficient value as the test statistic while controlling for number of observations (Franks et al . 2020), (3) pre-network permutation tests with the coefficient value as the test statistic, (4) pre-network permutation tests with the t statistic as the test statistic, and (5) double permutation tests with the coefficient as the test statistic.…”
Section: Testing the Robustness Of The Double Permutation Approachmentioning
confidence: 99%
“…In summary, our results suggest that double permutation tests are most useful when sampling biases or other nuisance effects might be an issue, and especially when the impact of such effects are expected but not well understood. This method is an alternative to model-fitting methods, such as fitting generalized additive models that can handle non-linearity in the relationship between sampling intensity and a network metric of interest (Franks et al . 2020).…”
Section: The Double Permutation Approach Is Robust To Type I and Typementioning
confidence: 99%
See 2 more Smart Citations